Association between body composition and weight retention from early pregnancy to 42 days postpartum: a retrospective cohort study - Yan Li; Xia Li; Yang Li; Bin Zhao; Jiaying Yuan; Kui Lan (BMJ Open)
Objective To evaluate the association between body composition from early pregnancy to 42 days postpartum and postpartum weight retention (PPWR).Design This retrospective cohort study was conducted at Chengdu Shuangliu Maternal and Child Health Care Hospital from June 2020 to December 2021.Setting The study was conducted in Sichuan Province, southwestern China.Participants A total of 673 pregnant women at 6–13 weeks of gestation were included.Outcome measures Demographic and health information of participants was collected from the electronic medical record system using a self-designed questionnaire. Body fat percentage (PBF), fat mass (FM), fat-free mass (FFM), lean mass (LM) and protein were measured using bioelectrical impedance analysis. Logistic regression and restricted cubic spline (RCS) analyses were performed to examine the association between body composition and PPWR.Results During early pregnancy, compared with the bottom quartile group, women in the top quartile group of PBF and FM levels had a 51% (95% CI 0.24 to 0.99) and 64% (95% CI 0.17 to 0.76) lower risk of PPWR, respectively. For each SD increase in PBF and FM levels, the risk of PPWR decreased by 29% (95% CI 0.55 to 0.91) and 35% (95% CI 0.50 to 0.85), respectively. In contrast, at 42 days postpartum, for each SD increase in PBF, FM, FFM and LM levels, the PPWR risk elevated by 251% (95% CI 2.70 to 4.62), 315% (95% CI 3.15 to 5.57), 56% (95% CI 1.30 to 1.89), and 71% (95% CI 1.42 to 2.09). RCS analysis revealed that PBF and FM levels during early pregnancy were negatively correlated with the risk of PPWR (p-overall <0.001, p-non-linear=0.444–0.501), while ‘J’-shaped relationships were observed for PBF, FM, FFM and LM levels at 42 days postpartum (p-overall <0.001, p-non-linear=0.306–0.734).Conclusions PBF and FM during early pregnancy are negatively associated with PPWR, whereas PBF, FM, FFM and LM at 42 days postpartum show positive associations. Among these, changes in FM contribute the most to PPWR.